DIGITAL TECHNOLOGIES IN THE OIL AND GAS INDUSTRY - Yu. Linnik; M. Kiryukhin (Вестник университета)
The issues of changing the traditional activities of enterprises towards the use of digital technologies have been considered. The results of studies of the implementation of digital technologies in the activities of companies in the oil and gas industry have been adduced. The technologies of intellectual wells, intellectual fields, deserted hydrocarbon production, which form the digital oil and gas industry, have been reviewed. The practice of applying digital technologies in the domestic and foreign fuel and energy complexes has been analyzed. Current trends in the development of digital technologies for the oil and gas industry have been identified. The obstacles, encountered in the development of the oil and gas sector, have been investigated.